(untitled) (Al-Aasar, 2025)
This study examines how modern Urdu novels portray educational consciousness, highlighting its role in shaping critical thinking and societal transformation. Starting from Deputy Nazir Ahmad’s Mirat-ul-Uroos, which laid the foundation for educational themes in Urdu fiction, contemporary novelists have expanded the discourse by addressing educational challenges, institutional flaws, and social inequalities. Dr. Shahid Siddiqui’s Aadhe Adhoore Khwab critiques rote learning and promotes student-centered education. Dr. Maqbool Nisar Malik’s University explores the commercialization of higher education. Muhammad Hameed Shahid’s Mitti Aadmi Khaati Hai emphasizes education’s role in self-awareness. Asghar Nadeem Syed’s Tooti Hui Tanab Udhar critiques the colonial dual education system, while Akhtar Raza Saleemi’s Jandar symbolizes the clash between tradition and modern education. These novels depict education not just as academic learning but as a transformative force shaping individual and collective identities. By integrating educational themes, Urdu novelists contribute to a broader discourse on literacy, critical thinking, and social progress in Pakistan.